Formulasi Sediaan Nanopartikel Ekstrak Bonggol Nanas (Ananas Comosus (L).(Merr) sebagai Antimikroba - Dian Eleveny Martha Flareyanti; Fahleni Fahleni; Deni Rahmat (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Pineapple stem contains bromelain enzyme with highest concentration compared to the other parts. The aim of the research was to formulate an anti dandruff creambath containing nanoparticles of pineapple stem which was physically and chemically stable and could inhibit the growth of Pityrosporum ovale. The pineapple stem extract was then formulated into nanoparticles prepared by cross-linking method using chitosan. The resulting nanoparticles were dried using freeze drying. The dried powder of extract was used to determine the minimum inhibitory concentration (MIC) against Pityrosporum ovale. The zone of inhibition of extract and nanoparticles were measured at the MIC. The extracts were then formulated into anti dandruff creambath. The creambath in the concentration of 3% (MIC) whereas the nanoparticles were formulated in the consentration of 1, 2, 3 fold MIC. Each formula was evaluated for its physical characteristics including organoleptics, homogenity, viscosity and flow properties, spread ability and for its chemical characteristic pH value. The stability was performed for one month at temperature of 25 oC and 40 oC. The results showed that the nanoparticles have particle size of 860.03 nm and zeta potensial of 18.63 mV. The best formula was formula IV with inhibitory zone of 17 mm, and had stable organoleptic properties, homogenity, viscosity and flow properties, and pH value, as well as capaability of spreading with diameter of 4817.53 mm. Accordingly the nanoparticlesin creambath could increase the antimicrobial activity.